2021
DOI: 10.1021/acscatal.1c04153
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven N-Heterocyclic Carbene Catalysis Using Alkylborates

Abstract: Radical–radical coupling, the selective reaction between two different radical species, has contributed to the methodology for connecting bulky units. Light-driven N-heterocyclic carbene (NHC) organocatalysis is recognized as a state-of-the-art methodology enabling radical–radical coupling. The catalytic process involves forming an acyl azolium intermediate from the NHC catalyst and an acyl donor, followed by single electron reduction of this key intermediate, which is largely dependent on the photoredox catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 43 publications
0
55
0
Order By: Relevance
“…Since these pioneering studies, important contributions that enable the direct assembly of functional molecules with broad utility have been made to this field. Recently, Ohmiya and coworkers reported that the NHC-catalyzed SET process has important potential for carbon–carbon bond formation through radical–radical coupling 42 46 . Moreover, asymmetric radical reactions under chiral NHC catalysis offer unique opportunities for unconventional approaches to the synthesis of chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Since these pioneering studies, important contributions that enable the direct assembly of functional molecules with broad utility have been made to this field. Recently, Ohmiya and coworkers reported that the NHC-catalyzed SET process has important potential for carbon–carbon bond formation through radical–radical coupling 42 46 . Moreover, asymmetric radical reactions under chiral NHC catalysis offer unique opportunities for unconventional approaches to the synthesis of chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 30 NHC-catalyzed light-induced direct and conjugative cross-coupling of acyl Imidazoles with alkylborates 42 Ohmiya reported NHC-catalyzed direct and conjugative cross-coupling of acyl Imidazoles with alkylborates under the illumination of blue light (Scheme 30). 42 Compared with the Template for SYNTHESIS Thieme previous method using NHPI ester as alkyl radical precursor, 12 the alkene alkylacylation demonstrates a much broader substrate applicability. The redox photocatalyst is unnecessary in the protocol, because the photoexcitable borates possess sufficient reduction potential (E1/2 = ca.…”
Section: Organoborane Reagentsmentioning
confidence: 99%
“…Scheme 30 NHC-catalyzed light-induced direct and conjugative crosscoupling of acylimidazoles with alkylborates 42 Potassium trifluoroborate salts are convenient and stable reagents for alkyl transfer, and can also yield an alkyl radical under photoredox conditions. The synthesis of aryloxy ketones via NHC/photoredox catalyzed aryloxylacylation of olefins with trifluoroborate salts was described by Scheidt and co-workers (Scheme 31).…”
Section: Organoborane Reagentsmentioning
confidence: 99%
“…The applicability of this activation mode has been demonstrated in many reactions including addition to heteroarenes, Giese‐type addition, and cross‐coupling [53] . Since these seminal studies, the group have made further advances in ligand design improving synthesis and absorption properties, [54] while the boronate has also been strategically aligned in NHC‐catalysed methods [55] …”
Section: Photocatalytic Activation Of the C−b Bondmentioning
confidence: 99%